An Analytical Review of Cross Cultural Child-Rearing and Care Practices: A Special Reference to India - Sharma, Prasun (Central European Journal of Educational Research, 2020)
Child-rearing is an individualist, social and cultural process. This paper proposes that Child-Rearing has invariable characteristics and huge diversity. It has been considered that cultural perspective may contribute to the understanding of such multiple forms of child-rearing. The present paper provides an analytical account of dominant factors of child-rearing and caring. The factors selection is done by reviewing the articles which have either more than 50 Google scholar citations or are indexed in top-class journals. It also aims to ascertain whether or not Indian child-rearing intrinsically has something different in its practices and which child-rearing patterns are global and common among all the countries. This article took majorly dominating factors in the area of child-rearing and provided a qualitative comparative account of India especially in relation to the world. Some factors are individualistic as parental attitude and the parent-child relationship. But the study found that corporal punishments, socialization and cultural factors have a strong impact on child-rearing. Altogether these factors affect the cognitive skills of children. The study will give a critical overview of child-rearing patterns in India and across the globe, which would be helpful for policymakers to create new policies and act accordingly.